1996
DOI: 10.1021/jp960932i
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Quenching of Excited Aliphatic Ketones and Diketones

Abstract: The oxygen quenching rate constants of aliphatic ketones (acetone, 2-pentanone, 2-hexanone, 4-heptanone) and diketones (biacetyl and camphorquinone) have been determined for the singlet- and triplet-excited state by time-resolved fluorescence and triplet transient absorption spectroscopy, and the quantum yields for singlet oxygen formation were measured. It was observed that the quenching rate constants for the singlet state of aliphatic ketones are considerably smaller than for their triplet states. The effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
1
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 69 publications
8
55
1
2
Order By: Relevance
“…This high value is fully in accord with earlier suggestions [48][49][50][51][52][53] that a pp* triplet is required for highly efficient singlet oxygen formation. Similar values were reported for other b-lapachones.…”
Section: Laser Flash Photolysis Studiessupporting
confidence: 92%
“…This high value is fully in accord with earlier suggestions [48][49][50][51][52][53] that a pp* triplet is required for highly efficient singlet oxygen formation. Similar values were reported for other b-lapachones.…”
Section: Laser Flash Photolysis Studiessupporting
confidence: 92%
“…the specific quenching efficiency of the oxygen molecule is an order of magnitude higher than in case of the singlet excited state. The T 1 + 3 O 2 → S 0 + O 2 ( 1 ∆ g ) reaction is spinallowed (to the extent of 1/9 spin-statistic factor) [15]. In contrast, the S 1 + 3 O 2 → S 0 + O 2 ( 1 ∆ g ) reaction is undoubtedly spin-forbidden, and so the possible alternative energy transfer process considered here does not seem to be very effective, either [15].…”
Section: Photophysical Studiesmentioning
confidence: 81%
“…•− was observed. Since the oxygen quenching of the singlet or/and triplet excited states of organic molecules to yield 1 O 2 has been extensively reported [22], it was suggested that the generation of 1 O 2 in this photochemical reaction of TC was reasonably attributable to the same mechanism. The fluorescence emission of TC aqueous solution before and after bubbling with argon did not change appreciably (data not shown), so the singlet TC excited state was not responsible for the generation of 1 O 2 and the quenching of triplet TC excited was suggested to yield 1 O 2 in this system.…”
Section: Mechanism On Photolysis Of Tcmentioning
confidence: 92%